2018
DOI: 10.3389/fphys.2018.01255
|View full text |Cite
|
Sign up to set email alerts
|

A Technique of Forced Expiratory Noise Time Evaluation Provides Distinguishing Human Pulmonary Ventilation Dynamics During Long-Term Head-Down and Head-Up Tilt Bed Rest Tests Simulating Micro and Lunar Gravity

Abstract: Estimating the effect of microgravity/hypogravity on pulmonary ventilation function remains topical. Recently developed acoustic techniques based on the evaluation of the forced expiratory noise time (FETa) were hypothesized to be a promising tool for this aim. The aim of the protocol is to study the effect of two different modalities of bed rest space simulations (microgravity and lunar gravity) on FETa and spirometric indices. The FETa in the frequency band of 200–2000 Hz, recorded above human trachea, was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is found that relative band-pass energies Ar 800–1000 and Ar 1400–1600 (Fig. 5 ) could distinguish studied subgroups (exp_1 vs exp_2) in the time interval the from 6th to 20th days of the experiment (2-factor ANOVA) no less successfully than FET a in Malaeva et al (2018) .…”
Section: Results and Discussion Of Some Diagnostic Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is found that relative band-pass energies Ar 800–1000 and Ar 1400–1600 (Fig. 5 ) could distinguish studied subgroups (exp_1 vs exp_2) in the time interval the from 6th to 20th days of the experiment (2-factor ANOVA) no less successfully than FET a in Malaeva et al (2018) .…”
Section: Results and Discussion Of Some Diagnostic Applicationsmentioning
confidence: 94%
“…As for microgravity simulation, Malaeva et al (2018) previously studied postural simulation of microgravity by means of head-down −6° test (exp_1, five males) and lunar gravity by means of head-up +9.6° test (exp_2, six males) during a 20-day experiment. The reason for postural changes was a simulation of a lunar mission with part ofa crew in an orbital device (microgravity) and another part on the Moon's surface (lunar gravity).…”
Section: Results and Discussion Of Some Diagnostic Applicationsmentioning
confidence: 99%
“…A pulmonary function test was performed before and after the interventions. It was performed before the cardiopulmonary exercise testing (CPET) to measure forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), and the ratio between them (FEV1/FVC), and MIP [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reactions of respiratory system to low-frequency acoustic effects change depending on their frequency and intensity and depend on a person's anthropometric characteristics [16][17][18][19]. Respiratory reactions include chest and diaphragm vibration with the main frequency of the influence, the depth and rhythm of respiration change, chest excursion cessation without gaseous metabolism in lungs violation.…”
Section: Introductionmentioning
confidence: 99%